Interaural Asymmetries Revealed by Dichotic Listening Tests in Normal and Dyslexic Children - Moncrieff, Deborah W.; Musiek, Frank E. (Journal of the American Academy of Audiology, 2002)
Normal and dyslexic right-handed children were assessed with three dichotic listening tests, the Dichotic Digits test, the Competing Words subtest of the SCAN, and the Dichotic Consonant-Vowel test. Performance was measured as both number and percentage of correct responses in the right and left ears. Laterality was defined as a simple difference in percentage between the two ears. Differences across the tests were revealed for all children, with the greatest differences occurring for left-ear responses. Only one dichotic listening test, Competing Words from the SCAN, produced a consistent right-ear advantage across all of the children tested. Between groups of children, differences in performance and in laterality were demonstrated. Using a criterion of poorer than 76 percent correct for the left ear, the Competing Words subtest of the SCAN identified 7 of the 10 dyslexic children as abnormal, with no false alarms in the control group.
Keywords: Children; dichotic listening; dyslexia; interaural asymmetry